The Use of Serial Picture Media in Improving the English Speaking Skills of Class XI IPA 1 Students of SMA Negeri 12 Sinjai - Rahmiati (Universitas Islam Ahmad Dahlan (UIAD), 2022)
This study aims to investigate the development of students English speaking skills using serial picture media. This type of research is classroom action research. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The research subjects are 23 students of class XI IPA 1 at SMA Negeri 12 Sinjai. This research study uses observation, documentation, and interviews as data collection tehniques. The colected data is the analysed using descriptive quantitative and qualitative. The indicator of success in this study is that when the 80% of students are able to speak English through the media of serial images. The results of this study indicate that there is an increase in students' English speaking skills through the use of serial pictures at SMAN 12 Sinjai. This is proven by the increase in the average English speaking skills of students in the Pre-action of 60.04%, increasing to 78.08% in the Action Cycle I, and reaching 90.51% in the Action Cycle II. The students' English speaking skills increase after the researcher gave the actions carried out through several stages and processes which are 1) The teacher shows several serial pictures to students and divides them into groups, then explains what to do with these pictures; 2) Students are given the task of speaking English related to the serial picture that they are holding. This activity is carried out alternately between students; 3) Students are given the opportunity to speak English in front of their classmates or online; and 4) The teacher always provides motivation so that students become enthusiastic and enthusiastic in participating in English speaking activities.